Collaborative Policy Strategies for Addressing School Dropout in Archipelagic Areas: Evidence from Pulau Laut Utara, Indonesia - Taufikurrahman Taufikurrahman; Muhammad Riduansyah Syafari; Siswanto Siswanto (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study examines policy strategies for addressing school dropout in Pulau Laut Utara District, Kotabaru Regency, Indonesia, an archipelagic area characterized by economic vulnerability, geographical barriers, and fragmented educational services. Using a qualitative design informed by participatory action research, data were collected through interviews, observation, and policy document analysis involving local government officials, school leaders, teachers, PKBM managers, parents, and out-of-school children. The findings indicate that dropout is not a sudden event but a gradual process shaped by household poverty, indirect schooling costs, weak learning motivation, distance to school, and limited cross-sectoral coordination. Existing policies include preventive, curative, and rehabilitative strategies; however, their implementation remains constrained by fragmented data systems, weak case-based coordination, and stigma toward nonformal education. The study contributes to place-based education policy by proposing an integrated early warning system, community-based PKBM strengthening, and collaborative governance across education, social protection, and village-level institutions.